Exterior package for all-solid battery and all-solid battery using the same

A laminated structure with specific adhesive layers and materials addresses adhesion and heat resistance issues in lithium-ion batteries, ensuring robust performance across temperature variations.

JP2025015860AInactive Publication Date: 2025-01-30TOPPAN HOLDINGS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024204095
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing laminated lithium-ion batteries face issues with insufficient inter-layer adhesion and reduced sealing properties in high-temperature environments due to inadequate exterior materials, leading to decreased laminated strength and molding integrity.

Method used

A laminated structure comprising a base layer, first and second adhesive layers, and a barrier layer, with specific transmittance ratios and materials like multifunctional isocyanate compounds, ensures strong adhesion and heat resistance, enhancing both room temperature and high-temperature performance.

Benefits of technology

The solution provides excellent laminate intensity and deep squeezing molding capabilities, maintaining structural integrity under varying temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015860000001_ABST
    Figure 2025015860000001_ABST
Patent Text Reader

Abstract

To provide an exterior material for power storage device which can secure the excellent lamination strength under both of a room-temperature environment and a high-temperature environment, and has the excellently deep-drawing moldability, and a power storage device using the same.SOLUTION: An exterior material for power storage device is made of a laminate that includes at least a substrate layer 11, a first adhesive layer 12a, a barrier layer 13, a second adhesive layer 12b and a sealant layer 16 in this order. When the substrate layer is removed, the first adhesive layer is exposed, and measurement is performed with the attenuated total reflection of the Fourier transformation infrared spectroscopic analysis method from the outermost surface side of the exposed adhesive layer, a transmission factor T0 of a baseline, a minimum value T1 of the transmission factor detected within a range from 2100 cm-1 to 2400 cm-1, and a minimum value T2 of the transmission factor detected within a range from 1670 cm-1 to 1700 cm-1 satisfy the relationship of 0.06≤(T0-T1) / (T0-T2)≤0.4.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an exterior material for an electricity storage device that is excellent in both heat resistance and moldability, and an electricity storage device using the same. [Background technology]

[0002] Known examples of power storage devices include secondary batteries such as lithium ion batteries, nickel metal hydride batteries, and lead storage batteries, as well as electrochemical capacitors such as electric double layer capacitors. Due to the miniaturization of portable devices or the limitations of installation space, there is a demand for further miniaturization of power storage devices, and lithium ion batteries with high energy density have attracted attention. Metal cans have traditionally been used as exterior materials for lithium ion batteries, but multilayer films that are lightweight, have high heat dissipation properties, and can be produced at low cost have come to be used.

[0003] A lithium ion battery using the above multilayer film as an exterior material is called a laminated lithium ion battery. The exterior material covers the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) and prevents moisture from penetrating into the battery. A laminated lithium ion battery is manufactured, for example, by forming a recess in a part of the exterior material by cold forming, accommodating the battery contents in the recess, folding back the remaining part of the exterior material, and heat sealing the edges (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-101765 A Summary of the Invention [Problem to be solved by the invention]

[0005] Meanwhile, research and development is being conducted on a power storage device called an all-solid-state battery as a next-generation battery of lithium-ion batteries. An all-solid-state battery is characterized by using a solid electrolyte as the electrolyte, rather than an organic electrolyte. While a lithium-ion battery cannot be used at temperatures higher than the boiling point of the electrolyte (about 80°C), an all-solid-state battery can be used at temperatures exceeding 100°C, and the conductivity of lithium ions can be increased by operating it under high temperature conditions (for example, 100 to 150°C).

[0006] However, when a laminated all-solid-state battery is manufactured using the above-mentioned multilayer film as an exterior material, if the heat resistance of the exterior material is insufficient, the interlayer adhesion cannot be ensured in a high-temperature environment, and the laminate strength may decrease, resulting in a decrease in the sealing property of the package of the all-solid-state battery. As shown in Patent Document 1, the exterior material has a structure in which, for example, a base material layer, a metal foil layer (barrier layer), and a sealant layer are laminated via an adhesive layer or the like, but the adhesion between the base material layer and the metal foil layer is likely to decrease in a high-temperature environment. In addition, epoxy-based adhesives are known as heat-resistant adhesives, but the cured product of the epoxy-based adhesive is likely to be highly brittle, and the deep drawability and laminate strength required for the exterior material and room temperature environment are likely to be insufficient.

[0007] The present disclosure has been made in consideration of the above-mentioned problems, and aims to provide an exterior material for an energy storage device that can ensure excellent laminate strength both in room temperature and high temperature environments and also has excellent deep draw formability, and an energy storage device using the same. [Means for solving the problem]

[0008] In order to solve the above problems, the present disclosure provides a laminate including at least a base layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a sealant layer in this order, The base material layer is removed to expose the first adhesive layer. When the exposed adhesive layer is measured from the outermost surface side by attenuated total reflection of Fourier transform infrared spectroscopy, the transmittance at baseline T0 and the transmittance at 2100 cm-1 From 2400cm -1 The minimum transmittance T1 detected in the range of 1670cm -1 From 1700cm -1 The present invention provides an exterior material for an electricity storage device, characterized in that the minimum value T2 of transmittance detected in the range satisfies the relationship 0.06≦(T0-T1) / (T0-T2)≦0.4.

[0009] When the relationship 0.06≦(T0-T1) / (T0-T2)≦0.4 is satisfied, the tensile strength and breaking elongation of the first adhesive layer become close to those of each layer (mainly the barrier layer and the substrate), resulting in improved moldability. In addition, when a molded product using the packaging material of the present invention is exposed to a high-temperature environment (150°C), the reaction between unreacted curing agents is promoted, raising the Tg of the first adhesive layer and improving heat resistance.

[0010] In the electrical storage device packaging material, the first adhesive layer may contain a polyfunctional isocyanate compound, and the polyfunctional isocyanate compound may be at least one polyfunctional isocyanate compound selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing an aromatic ring in the molecular structure. By defining the structure of the isocyanate compound as alicyclic and containing a benzene ring, it is possible to improve initial adhesion and heat resistance.

[0011] In the above-mentioned exterior material for a storage battery device, the first adhesive layer may contain a urethane resin formed from at least one polyol selected from the group consisting of polyester polyol, acrylic polyol, and polycarbonate diol, and the polyfunctional isocyanate polymer. When the polyol component is selected from the three types of polyester polyol, acrylic polyol, and polycarbonate diol (PCD), heat resistance and moldability are improved. Among them, polyester polyol is preferable.

[0012] In the exterior packaging material for a power storage device, the ratio of the number of isocyanate groups contained in the polyfunctional isocyanate polymer to the number of hydroxyl groups contained in the polyol may be 5 to 60. By setting the NCO / OH ratio to a value within this range, the laminate strength in a high-temperature environment can be improved and a decrease in moldability can be prevented.

[0013] In the above-mentioned exterior packaging material for a storage battery device, the coating amount of the urethane resin after drying is 2.0 g / m 2 More than 6.0g / m 2 If the coating amount is less than 2.0 g, the adhesive layer will be thin, which may result in poor stress dispersion and poor moldability. On the other hand, if the coating amount is increased, the adhesive layer will become thicker, which will improve moldability due to improved stress dispersion. However, if the coating amount is more than 6.00 g / m 2 Even if the coating amount is increased, no significant improvement in moldability is observed, and the upper limit of the coating amount is set to 6.00 g / m due to cost considerations, etc. 2 It is preferable to set the following.

[0014] In the packaging material for a power storage device, the barrier layer may be made of aluminum foil, which has an excellent overall balance of barrier properties, stretchability, cost, and the like.

[0015] In the packaging material for an electricity storage device, the barrier layer may have a thickness of 15 to 100 μm, which provides good moldability and reduces costs.

[0016] In the above-mentioned exterior material for a storage battery device, a corrosion prevention treatment layer may be provided between the first adhesive layer and the barrier layer, or between the second adhesive layer and the barrier layer, or both of them. The chemical adhesion to the adhesive layer is improved, so that moldability is improved. In addition, corrosion resistance against hydrogen sulfide generated when a sulfide is used for the solid electrolyte can be imparted.

[0017] In the electrical storage device packaging material, the substrate may be made of a polyamide film or a polyester film. By using a substrate having excellent toughness and heat resistance, the heat resistance and moldability can be improved.

[0018] The exterior material for a power storage device may be for an all-solid-state battery.

[0019] The present disclosure also provides an electric storage device including an electric storage device main body, a current extracting terminal extending from the electric storage device main body, and an exterior material for an electric storage device according to the present disclosure, the exterior material sandwiching the current extracting terminal and housing the electric storage device main body. The electric storage device may be an all-solid-state battery. Effect of the Invention

[0020] According to the present disclosure, it is possible to provide an exterior material for an electricity storage device that can ensure excellent laminate strength both in room temperature and high temperature environments and also has excellent deep draw formability, and an electricity storage device using the same. [Brief description of the drawings]

[0021] [Figure 1] 1 is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 3] 1 is a perspective view of an electricity storage device according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.

[0023] [Exterior materials for power storage devices] Fig. 1 is a cross-sectional view showing a schematic diagram of an embodiment of the exterior material for a power storage device according to the present disclosure. As shown in Fig. 1, the exterior material (exterior material for a power storage device) 10 of this embodiment is a laminate including a base layer 11, a first adhesive layer 12a provided on one side of the base layer 11, a barrier layer 13 having first and second corrosion prevention treatment layers 14a, 14b on both sides provided on the side of the first adhesive layer 12a opposite the base layer 11, a second adhesive layer 12b provided on the side of the barrier layer 13 opposite the first adhesive layer 12a, and a sealant layer 16 provided on the side of the second adhesive layer 12b opposite the barrier layer 13. Here, the first corrosion prevention treatment layer 14a is provided on the surface of the barrier layer 13 facing the base layer 11, and the second corrosion prevention treatment layer 14b is provided on the surface of the barrier layer 13 facing the sealant layer 16. In the exterior packaging material 10, the base material layer 11 is the outermost layer and the sealant layer 16 is the innermost layer. That is, the exterior packaging material 10 is used with the base material layer 11 facing the exterior side of the electricity storage device and the sealant layer 16 facing the interior side of the electricity storage device.

[0024] In the exterior material 10 of this embodiment, when the base material layer 11 is removed and the exposed outermost surface side of the first adhesive layer 12a is measured by attenuated total reflection in Fourier transform infrared spectroscopy, the transmittance T0 of the baseline and the transmittance at 2100 cm -1 From 2400cm -1 The minimum transmittance T1 detected in the range of 1670cm -1 From 1700cm -1 The minimum transmittance value T2 detected in this range satisfies the relationship 0.06≦(T0−T1) / (T0−T2)≦0.4.

[0025] Each layer constituting the packaging material 10 will now be described in detail.

[0026] <Base material layer 11> The base layer 11 provides heat resistance in the sealing process when manufacturing the electricity storage device and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for a large-scale electricity storage device, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.

[0027] The base layer 11 is preferably a layer made of a resin film formed of an insulating resin. Examples of the resin film include stretched or unstretched films such as polyester film, polyamide film, polyimide film, and polypropylene film. The base layer 11 may be a single layer film made of any of these resin films, or a laminate film made of two or more of these resin films.

[0028] Among these, polyester film and polyamide film are preferable as the base layer 11 because of their excellent moldability, and polyester film is more preferable. These films are preferably biaxially stretched films. Examples of polyester resins constituting polyester films include polyethylene terephthalate (PET). Examples of polyamide resins constituting polyamide films include nylon 6, nylon 6,6, copolymers of nylon 6 and nylon 6,6, nylon 6,10, polymetaxylylene adipamide (MXD6), nylon 11, nylon 12, etc. Among polyamide films, nylon 6 (ONy) is preferable because of its excellent heat resistance, puncture strength, and impact strength.

[0029] Examples of the stretching method for the biaxially stretched film include a sequential biaxial stretching method, a tubular biaxial stretching method, a simultaneous biaxial stretching method, etc. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by a tubular biaxial stretching method.

[0030] In addition, the base layer 11 preferably has a peak melting temperature higher than the peak melting temperature of the sealant layer 16. When the sealant layer 16 has a multi-layer structure, the peak melting temperature of the sealant layer 16 means the peak melting temperature of the layer with the highest peak melting temperature. The peak melting temperature of the base layer 11 is preferably 290°C or higher, more preferably 290 to 350°C. Examples of resin films that can be used as the base layer 11 and have a peak melting temperature in the above range include nylon film, PET film, polyamide film, polyimide film, and polyphenylene sulfide film (PPS film). As the base layer 11, a commercially available film may be used, or the base layer 11 may be formed by coating (application of a coating liquid and drying). The base layer 11 may have a single layer structure or a multi-layer structure, and may be formed by applying a thermosetting resin. In addition, the base layer 11 may contain, for example, various additives (for example, a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, etc.).

[0031] The difference (T11-T16) between the peak melting temperature T11 of the base layer 11 and the peak melting temperature T16 of the sealant layer 16 is preferably 20° C. or more. When this temperature difference is 20° C. or more, deterioration of the appearance of the packaging material 10 caused by heat sealing can be more sufficiently suppressed.

[0032] The thickness of the substrate layer 11 is preferably 5 to 50 μm, more preferably 6 to 40 μm, further preferably 10 to 30 μm, and particularly preferably 12 to 30 μm. When the thickness of the substrate layer 11 is 5 μm or more, the pinhole resistance and insulating properties of the packaging material for an electricity storage device 10 tend to be improved. If the thickness of the substrate layer 11 exceeds 50 μm, the total thickness of the packaging material for an electricity storage device 10 becomes large, which is undesirable because it may be necessary to reduce the electric capacity of the battery.

[0033] <First adhesive layer 12a> The first adhesive layer 12a is a layer that bonds the base material layer 11 and the barrier layer 13. In the exterior material 10 of the present embodiment, the first adhesive layer 12a contains a urethane resin formed from at least one polyol selected from the group consisting of polyether polyol, polyester polyol, acrylic polyol, and polycarbonate diol, and a polyfunctional isocyanate compound, and the polyfunctional isocyanate compound is composed of at least one polyfunctional isocyanate compound selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing an aromatic ring in the molecular structure.

[0034] In addition, when the first adhesive layer 12a is exposed by peeling off the base material layer 11 and measured from the outermost surface side of the exposed first adhesive layer 12a by attenuated total reflection by Fourier transform infrared spectroscopy, the transmittance of the baseline T0 and the transmittance of the 2100 cm -1 From 2400cm -1 The minimum transmittance T1 detected in the range of 1670cm -1 From 1700cm -1 The minimum transmittance value T2 detected in this range satisfies the relationship 0.06≦(T0−T1) / (T0−T2)≦0.4.

[0035] In the IR spectrum obtained by measuring attenuated total reflection by Fourier transform infrared spectroscopy, -1 From 2400cm -1 The peak detected in the range of 1670 cm is the peak of the carbonyl group derived from the isocyanate group. -1 From 1700cm -1The peak detected in the range is the peak of the carbonyl group derived from the urethane bond. When the ratio of the isocyanate group to the urethane bond satisfies 0.06≦(T0-T1) / (T0-T2)≦0.4, the adhesive layer contains unreacted isocyanate groups and urea resins and biuret resins generated by the reaction of some of the curing agents with each other. Due to the active hydrogen groups present in the urea resins and biuret resins, the tensile strength and breaking elongation of the adhesive layer become closer to the values ​​of each layer (mainly the barrier layer and the substrate), and as a result, the moldability is improved. Furthermore, when the molded product of the present invention is exposed to a high temperature environment (150°C), the reaction between the unreacted curing agents is promoted. The increase in the urea resins and biuret resins increases the Tg of the adhesive layer, improving the heat resistance.

[0036] In contrast, when (T0-T1) / (T0-T2)<0.06, there are two patterns: the base agent and the curing agent react quantitatively under the condition of NCO / OH≒1.0, and the curing agents react quantitatively with each other under the condition of NCO / OH>1.0. In the former case, the Tg of the adhesive layer drops significantly compared to a high-temperature environment (150°C), causing cohesive failure of the adhesive layer. In the latter case, almost all of the curing agent has reacted during the aging stage, and the adhesive layer is more brittle than when 0.06≦(T0-T1) / (T0-T2)≦0.4 is satisfied, resulting in a significant decrease in moldability.

[0037] In addition, when (T0-T1) / (T0-T2)>0.4, there is a pattern where there is an excess of unreacted curing agent in the adhesive layer. If this adhesive layer is exposed to a high-temperature environment, there is a risk of foaming due to the reaction between the excess curing agents. This causes delamination in a high-temperature environment, which reduces heat resistance.

[0038] In the first adhesive layer 12a, the polyfunctional isocyanate compound may contain at least one selected from the group consisting of an adduct of tolylene diisocyanate (TDI-adduct), an adduct of hexamethylene diisocyanate, a biuret and a nurate of hexamethylene diisocyanate, a biuret and a nurate of tolylene diisocyanate, an adduct, a biuret and a nurate of diphenylmethane diisocyanate, and an adduct, a biuret and a nurate of xylylene diisocyanate, or may contain a TDI-adduct. By using such a polyfunctional isocyanate compound in combination with IPDI-nurate, the laminate strength and deep drawing moldability under room temperature environment can be further improved.

[0039] When the polyfunctional isocyanate compound contains a TDI-adduct, the ratio (NCOA / NCOB) of the number of isocyanate groups (NCOA) derived from IPDI-nurate to the number of isocyanate groups (NCOB) derived from the TDI-adduct may be 0.05 to 20. From the viewpoint of heat resistance, the ratio (NCOA / NCOB) may be 0.3 to 6, 2 to 4, or 3. The ratio (NCOA / NCOB) may also be 7 to 20. When this ratio is 0.05 or more, the laminate strength in a high-temperature environment can be sufficiently ensured, and the occurrence of delamination when exposed to high temperatures after deep drawing can be sufficiently suppressed. When the ratio is 20 or less, the laminate strength and deep drawing moldability in a room temperature environment can be further improved.

[0040] In the first adhesive layer 12a, the ratio (NCO / OH) of the number of isocyanate groups contained in the polyfunctional isocyanate compound to the number of hydroxyl groups contained in the polyester polyol resin may be 2 to 60, 5 to 50, or 10 to 30. When this ratio is 2 or more, the laminate strength in a high temperature environment can be further improved. When the ratio is 60 or less, the laminate strength in a room temperature environment and a high temperature environment can be further improved.

[0041] The thickness of the first adhesive layer 12a is not particularly limited, but from the viewpoint of obtaining desired adhesive strength, conformability, processability, and the like, the thickness is, for example, preferably 1 to 10 μm, and more preferably 3 to 7 μm.

[0042] The mass per unit area of ​​the first adhesive layer 12a is set to 2.0 to 6.0 g / m from the viewpoint of ensuring superior lamination strength both in room temperature and high temperature environments and obtaining superior deep drawability. 2 and 2.5 to 5.0 g / m 2 and 3.0 to 4.0 g / m 2 may be also possible.

[0043] <Barrier layer 13> The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the inside of the electricity storage device. The barrier layer 13 also has extensibility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, etc., or metal vapor deposition films, inorganic oxide vapor deposition films, carbon-containing inorganic oxide vapor deposition films, films provided with these vapor deposition films, etc. can be used. As the film provided with the vapor deposition film, for example, an aluminum vapor deposition film or an inorganic oxide vapor deposition film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, a metal foil is preferable, and an aluminum foil is more preferable, in terms of mass (specific gravity), moisture resistance, processability, and cost.

[0044] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. As the aluminum foil, an untreated aluminum foil may be used, but it is preferable to use an aluminum foil that has been degreased in order to impart electrolyte resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.

[0045] The thickness of the barrier layer 13 is not particularly limited, but is preferably 9 to 200 μm, more preferably 15 to 100 μm, in consideration of barrier properties, pinhole resistance, and processability. If it is thinner than 15 μm, moldability may decrease. If it is thicker than 100 μm, the weight energy density of the battery tends to decrease, and the cost increases.

[0046] <First and second corrosion prevention treatment layers 14a, 14b> The first and second corrosion prevention layers 14a and 14b are layers provided on the surface of the barrier layer 13 to prevent corrosion of the metal foil (metal foil layer) constituting the barrier layer 13. The first corrosion prevention layer 14a plays a role in increasing the adhesion between the barrier layer 13 and the first adhesive layer 12a. The second corrosion prevention layer 14b plays a role in increasing the adhesion between the barrier layer 13 and the second adhesive layer 12b. The first corrosion prevention layer 14a and the second corrosion prevention layer 14b may be layers of the same configuration or layers of different configurations. The first and second corrosion prevention layers 14a and 14b (hereinafter also simply referred to as "corrosion prevention layers 14a and 14b") are formed, for example, by degreasing, hydrothermal conversion, anodizing, chemical conversion, or a combination of these treatments.

[0047] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone or a mixture of these. In addition, by using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid as described above, not only can the aluminum be degreased, but also a passive aluminum fluoride can be formed, which is effective in terms of corrosion resistance, particularly when an aluminum foil is used for the barrier layer 13. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.

[0048] An example of the hydrothermal modification treatment is a boehmite treatment in which an aluminum foil is immersed in boiling water containing added triethanolamine.

[0049] An example of the anodizing treatment is an alumite treatment.

[0050] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, and various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the barrier layer 13.

[0051] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely, hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. When using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the barrier layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layers 14a and 14b.

[0052] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.

[0053] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) having excellent corrosion resistance. Therefore, since a bicontinuous structure is formed from the barrier layer 13 using the aluminum foil to the corrosion prevention treatment layers 14a, 14b, the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layers 14a, 14b by a pure coating method that is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned, which has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to metal foils such as aluminum foils even with a general coating method.

[0054] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, ether-based, etc. Among these, water-based sols are preferred.

[0055] In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, etc. or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, lactic acid, etc. are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid in particular is expected to (1) stabilize the dispersion of the sol, (2) improve adhesion to the barrier layer 13 by utilizing the aluminum chelating ability of phosphoric acid, and (3) improve the cohesive force of the corrosion prevention treatment layers 14a, 14b (oxide layers) by easily causing dehydration condensation of phosphoric acid even at low temperatures.

[0056] Examples of the phosphoric acid or its salt include orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, or their alkali metal salts or ammonium salts. Among them, condensed phosphoric acid such as trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, and ultrametaphosphoric acid, or their alkali metal salts or ammonium salts are preferred for the functional expression in the exterior material 10. In addition, in consideration of the drying film-forming properties (drying ability, amount of heat) when the corrosion prevention treatment layers 14a, 14b made of rare earth element oxide are formed by various coating methods using the sol of the rare earth element oxide, sodium salts are more preferred because of their excellent dehydration condensation properties at low temperatures. As the phosphate, water-soluble salts are preferred.

[0057] The compounding ratio of phosphoric acid (or a salt thereof) to the rare earth element oxide is preferably 1 to 100 parts by mass per 100 parts by mass of the rare earth element oxide. If the compounding ratio is 1 part by mass or more per 100 parts by mass of the rare earth element oxide, the rare earth element oxide sol becomes more stable, and the function of the exterior material 10 becomes better. The compounding ratio is more preferably 5 parts by mass or more per 100 parts by mass of the rare earth element oxide. Also, if the compounding ratio is 100 parts by mass or less per 100 parts by mass of the rare earth element oxide, the function of the rare earth element oxide sol is improved. The compounding ratio is more preferably 50 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of the rare earth element oxide.

[0058] The corrosion prevention treatment layers 14a, 14b formed from the rare earth oxide sol are aggregates of inorganic particles, and therefore the cohesive strength of the layers themselves may be reduced even after the drying and curing process. Therefore, in this case, the corrosion prevention treatment layers 14a, 14b are preferably compounded with the following anionic polymer or cationic polymer to supplement the cohesive strength.

[0059] Examples of the anionic polymer include polymers having a carboxy group, such as poly(meth)acrylic acid (or a salt thereof) or a copolymer obtained by copolymerizing poly(meth)acrylic acid as a main component. Examples of the copolymerization components of this copolymer include alkyl(meth)acrylate monomers (alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.); (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide (alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.), N-alkoxy(meth)acrylamide, N,N-dialkoxy(meth)acrylamide, (alkoxy)acrylamide, (meth ... Examples of the oxy group include a methoxy group, an ethoxy group, a butoxy group, and an isobutoxy group.) Amide group-containing monomers such as N-methylol (meth)acrylamide and N-phenyl (meth)acrylamide; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; glycidyl group-containing monomers such as glycidyl (meth)acrylate and allyl glycidyl ether; silane-containing monomers such as (meth)acryloxypropyl trimethoxysilane and (meth)acryloxypropyl triethoxylane; and isocyanate group-containing monomers such as (meth)acryloxypropyl isocyanate.

[0060] These anionic polymers play a role in improving the stability of the corrosion prevention treatment layers 14a, 14b (oxide layers) obtained using the rare earth element oxide sol. This is achieved by the effect of protecting the hard and brittle oxide layer with the acrylic resin component, and the effect of capturing (cation catcher) ion contaminants (especially sodium ions) derived from phosphates contained in the rare earth element oxide sol. In other words, if the corrosion prevention treatment layers 14a, 14b obtained using the rare earth element oxide sol contain alkali metal ions such as sodium or alkaline earth metal ions, the corrosion prevention treatment layers 14a, 14b tend to deteriorate starting from the places containing these ions. Therefore, the resistance of the corrosion prevention treatment layers 14a, 14b is improved by fixing the sodium ions and the like contained in the rare earth element oxide sol using the anionic polymer.

[0061] The anti-corrosion treatment layers 14a, 14b, which are a combination of an anionic polymer and a rare earth oxide sol, have the same anti-corrosion performance as the anti-corrosion treatment layers 14a, 14b formed by chromate treatment of an aluminum foil. The anionic polymer is preferably a structure in which a polyanionic polymer, which is essentially water-soluble, is crosslinked. Examples of crosslinking agents used to form this structure include compounds having an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group.

[0062] Examples of compounds having an isocyanate group include diisocyanates such as tolylene diisocyanate, xylylene diisocyanate or hydrogenated products thereof, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or hydrogenated products thereof, and isophorone diisocyanate; or polyisocyanates such as adducts obtained by reacting these isocyanates with polyhydric alcohols such as trimethylolpropane, biuret products obtained by reacting these isocyanates with water, or isocyanurate trimers; and blocked polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, or the like.

[0063] Examples of compounds having a glycidyl group include epoxy compounds obtained by reacting glycols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 14a,14b-butanediol, 1,6-hexanediol, and neopentyl glycol with epichlorohydrin; epoxy compounds obtained by reacting polyhydric alcohols such as glycerin, polyglycerin, trimethylolpropane, pentaerythritol, and sorbitol with epichlorohydrin; and epoxy compounds obtained by reacting dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid with epichlorohydrin.

[0064] Examples of compounds having a carboxy group include various aliphatic or aromatic dicarboxylic acids, etc. Also, poly(meth)acrylic acid and alkali (earth) metal salts of poly(meth)acrylic acid may be used.

[0065] Examples of compounds having an oxazoline group include low molecular weight compounds having two or more oxazoline units, and when a polymerizable monomer such as isopropenyloxazoline is used, copolymers of acrylic monomers such as (meth)acrylic acid, (meth)acrylic acid alkyl esters, and (meth)acrylic hydroxyalkyls can be mentioned.

[0066] Alternatively, the anionic polymer may be reacted with a silane coupling agent, more specifically, the carboxyl group of the anionic polymer may be selectively reacted with the functional group of the silane coupling agent, and the crosslinking point may be a siloxane bond. In this case, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-chloropropylmethoxysilane, vinyltrichlorosilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, etc. may be used. Among these, epoxysilane, aminosilane, and isocyanatesilane are preferred, especially considering the reactivity with the anionic polymer or its copolymer.

[0067] The ratio of these crosslinking agents to the anionic polymer is preferably 1 to 50 parts by mass, more preferably 10 to 20 parts by mass, per 100 parts by mass of the anionic polymer. If the ratio of the crosslinking agent is 1 part by mass or more per 100 parts by mass of the anionic polymer, the crosslinked structure is easily formed sufficiently. If the ratio of the crosslinking agent is 50 parts by mass or less per 100 parts by mass of the anionic polymer, the pot life of the coating liquid is improved.

[0068] The method for crosslinking the anionic polymer is not limited to the above-mentioned crosslinking agents, and may be a method for forming ionic crosslinks using titanium or zirconium compounds.

[0069] Examples of cationic polymers include polymers having amines, such as polyethyleneimine, ionic polymer complexes consisting of a polymer having polyethyleneimine and a carboxylic acid, primary amine-grafted acrylic resins in which a primary amine is grafted onto an acrylic main skeleton, polyallylamine or derivatives thereof, and cationic polymers such as aminophenol. Examples of polyallylamine include homopolymers or copolymers of allylamine, allylamine amide sulfate, diallylamine, and dimethylallylamine. These amines may be free amines or may be stabilized with acetic acid or hydrochloric acid. In addition, maleic acid, sulfur dioxide, and the like may be used as copolymer components. Furthermore, a type in which a primary amine is partially methoxylated to impart thermal crosslinking properties may be used, and aminophenol may also be used. In particular, allylamine or its derivatives are preferred.

[0070] The cationic polymer is preferably used in combination with a crosslinking agent having a functional group capable of reacting with amine / imine, such as a carboxy group or a glycidyl group. As the crosslinking agent to be used in combination with the cationic polymer, a polymer having a carboxylic acid that forms an ionic polymer complex with polyethyleneimine can also be used, and examples thereof include polycarboxylic acid (salt) such as polyacrylic acid or its ionic salt, or a copolymer having a comonomer introduced therein, and polysaccharides having a carboxy group such as carboxymethylcellulose or its ionic salt.

[0071] Cationic polymers are more preferred materials in terms of improving adhesion. In addition, cationic polymers are also water-soluble like the anionic polymers, so it is more preferred to form a crosslinked structure to impart water resistance. The crosslinking agent used to form a crosslinked structure in the cationic polymer can be the crosslinking agent described in the anionic polymer section. When a rare earth oxide sol is used as the corrosion prevention treatment layers 14a and 14b, a cationic polymer may be used as the protective layer instead of the anionic polymer.

[0072] The corrosion prevention treatment layer by chemical conversion treatment, such as chromate treatment, is formed on the aluminum foil by treating the aluminum foil with a chemical conversion treatment agent, particularly containing hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, or a salt thereof, and then forming a chemical conversion layer on the aluminum foil by applying a chromium or non-chromium compound. However, the above-mentioned chemical conversion treatment uses an acid as the chemical conversion treatment agent, which leads to deterioration of the working environment and corrosion of the coating device. On the other hand, unlike the chemical conversion treatment, such as chromate treatment, the above-mentioned coating type corrosion prevention treatment layers 14a and 14b do not need to form a gradient structure with respect to the barrier layer 13 using the aluminum foil. Therefore, the properties of the coating agent are not restricted by acidity, alkalinity, neutrality, etc., and a good working environment can be realized. In addition, the coating type corrosion prevention treatment layers 14a and 14b are preferable because alternatives to the chromate treatment using a chromium compound are required from the viewpoint of environmental hygiene.

[0073] From the above, examples of combinations of the above-mentioned coating-type corrosion prevention treatments include (1) only rare earth oxide sol, (2) only anionic polymer, (3) only cationic polymer, (4) rare earth oxide sol + anionic polymer (laminated composite), (5) rare earth oxide sol + cationic polymer (laminated composite), (6) (rare earth oxide sol + anionic polymer: laminated composite) / cationic polymer (multilayered), (7) (rare earth oxide sol + cationic polymer: laminated composite) / anionic polymer (multilayered), etc. Among them, (1) and (4) to (7) are preferred, and (4) to (7) are particularly preferred. However, this embodiment is not limited to the above combinations. For example, in the case of selecting a corrosion prevention treatment, a cationic polymer is a very preferable material because it has good adhesion to the modified polyolefin resin described below in the description of the adhesive resin layer. Therefore, in the case where the adhesive resin layer is composed of a modified polyolefin resin, it is possible to design the surface in contact with the adhesive resin layer to have a cationic polymer (for example, configurations such as (5) and (6)).

[0074] The corrosion prevention treatment layers 14a and 14b are not limited to the above-mentioned layers. For example, they may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be obtained. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent in which a rare earth oxide sol and a polycationic polymer or a polyanionic polymer are mixed in advance into a one-component solution can be used to obtain a layer having both corrosion prevention function and adhesion.

[0075] The mass per unit area of ​​the corrosion prevention layers 14a and 14b is 0.005 to 0.200 g / m2 regardless of whether the layer has a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the barrier layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention layers 14a and 14b can be calculated from their specific gravity.

[0076] From the viewpoint of easily maintaining the adhesion between the sealant layer and the barrier layer, the corrosion prevention treatment layers 14a, 14b may be in an embodiment containing, for example, cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment and contain a cationic polymer.

[0077] <Second adhesive layer 12b> The second adhesive layer 12b is a layer that bonds the barrier layer 13 on which the second corrosion prevention treatment layer 14b is formed, and the sealant layer 16. For the second adhesive layer 12b, a general adhesive for bonding a barrier layer and a sealant layer can be used. Specific examples of materials constituting the second adhesive layer 12b include polyurethane resins in which a bifunctional or higher isocyanate compound is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol.

[0078] The various polyols described above can be used alone or in combination of two or more kinds depending on the functions and performance required for the exterior material.

[0079] Depending on the performance required for the adhesive, various other additives and stabilizers may be blended with the polyurethane resin described above.

[0080] In the packaging material 10 of the present embodiment, the second adhesive layer 12b may be similar to the above-described first adhesive layer 12a.

[0081] The thickness of the second adhesive layer 12b is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, processability, and the like, it is preferably 1 to 10 μm, and more preferably 3 to 7 μm.

[0082] When the second adhesive layer 12b is the same as the first adhesive layer 12a, the mass per unit area of ​​the second adhesive layer 12b is set to 2.0 to 6.0 g / m2 from the viewpoint of ensuring superior lamination strength both in room temperature and high temperature environments and obtaining superior deep drawability. 2 and 2.5 to 5.0 g / m 2 and 3.5 to 4.5 g / m 2 may be also possible.

[0083] <Sealant layer 16> The sealant layer 16 is a layer that provides heat sealing to the exterior material 10. Examples of the sealant layer 16 include resin films made of polyolefin resins or polyester resins. The resins constituting the sealant layer 16 (hereinafter also referred to as "base resins") may be used alone or in combination of two or more.

[0084] Examples of polyolefin resins include low-, medium- or high-density polyethylene; ethylene-α-olefin copolymers; polypropylene; block or random copolymers containing propylene as a copolymerization component; and propylene-α-olefin copolymers.

[0085] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and polytrimethylene terephthalate (PTT) resin.

[0086] The sealant layer 16 may contain a polyolefin-based elastomer. The polyolefin-based elastomer may be compatible with the above-mentioned base resin or may not be compatible with it, and may contain both a compatible polyolefin-based elastomer that is compatible and a non-compatible polyolefin-based elastomer that is not compatible with it. Being compatible (compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 1 nm or more and less than 500 nm. Not being compatible (non-compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 500 nm or more and less than 20 μm.

[0087] When the base resin is a polypropylene resin, the compatible polyolefin elastomer may be, for example, a propylene-butene-1 random copolymer, and the incompatible polyolefin elastomer may be, for example, an ethylene-butene-1 random copolymer. The polyolefin elastomers may be used alone or in combination of two or more.

[0088] Furthermore, the sealant layer 16 may contain, as additive components, for example, slip agents, antiblocking agents, antioxidants, light stabilizers, flame retardants, etc. The content of these additive components is preferably 5 parts by mass or less, assuming that the total mass of the sealant layer 16 is 100 parts by mass.

[0089] The thickness of the sealant layer 16 is not particularly limited, but from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment, it is preferably in the range of 5 to 100 μm, more preferably in the range of 10 to 100 μm, and even more preferably in the range of 20 to 80 μm.

[0090] The sealant layer 16 may be either a single-layer film or a multi-layer film, and may be selected depending on the required function.

[0091] Although a preferred embodiment of the exterior material for a power storage device according to the present embodiment has been described in detail above, the present disclosure is not limited to such a specific embodiment, and various modifications and variations are possible within the scope of the gist of the present disclosure as described in the claims.

[0092] For example, FIG. 1 shows a case where anti-corrosion treatment layers 14a, 14b are provided on both sides of the barrier layer 13, but only one of the anti-corrosion treatment layers 14a, 14b may be provided, or no anti-corrosion treatment layer may be provided.

[0093] While Fig. 1 shows a case where the barrier layer 13 and the sealant layer 16 are laminated using the second adhesive layer 12b, the barrier layer 13 and the sealant layer 16 may be laminated using an adhesive resin layer 15 as in the exterior packaging material 20 for an electricity storage device shown in Fig. 2. In addition, in the exterior packaging material 20 for an electricity storage device shown in Fig. 2, the second adhesive layer 12b may be provided between the barrier layer 13 and the adhesive resin layer 15.

[0094] <Adhesive resin layer 15> The adhesive resin layer 15 is generally composed of an adhesive resin composition as a main component and additive components as necessary. The adhesive resin composition is not particularly limited, but preferably contains a modified polyolefin resin.

[0095] The modified polyolefin resin is preferably a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an acid anhydride, or an ester thereof.

[0096] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0097] The modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. For example, "Admer" manufactured by Mitsui Chemicals, Inc. and "Modic" manufactured by Mitsubishi Chemical Corporation are suitable for the modified polyolefin resin. Since such modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, the adhesive resin layer 15 can be given adhesion by utilizing the reactivity, and the electrolyte resistance can be improved. In addition, the adhesive resin layer 15 may contain various additives such as various compatible and incompatible elastomers, flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, and tackifiers, as necessary.

[0098] The thickness of the adhesive resin layer 15 is not particularly limited, but from the viewpoints of stress relaxation and moisture / electrolyte permeability, it is preferably the same as or less than that of the sealant layer 16 .

[0099] In addition, in the exterior packaging material 20 for a storage battery device, the total thickness of the adhesive resin layer 15 and the sealant layer 16 is preferably in the range of 5 to 100 μm, and more preferably in the range of 20 to 80 μm, from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment.

[0100] [Exterior material manufacturing method] Next, there will be described an example of a method for manufacturing the exterior packaging material 10 shown in Fig. 1. Note that the method for manufacturing the exterior packaging material 10 is not limited to the following method.

[0101] The manufacturing method of the exterior material 10 of this embodiment is roughly composed of a step of providing corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using a first adhesive layer 12a, a step of further laminating a sealant layer 16 via a second adhesive layer 12b to produce a laminate, and a step of, if necessary, subjecting the obtained laminate to an aging treatment.

[0102] (Laminating process of corrosion prevention treatment layers 14a, 14b on barrier layer 13) This step is a step of forming the corrosion prevention treatment layers 14a, 14b on the barrier layer 13. As described above, examples of the method include subjecting the barrier layer 13 to a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, or a chemical conversion treatment, or applying a coating agent having corrosion prevention properties.

[0103] Furthermore, when the corrosion prevention treatment layers 14a, 14b are multiple layers, for example, a coating liquid (coating agent) constituting the lower corrosion prevention treatment layer (barrier layer 13 side) may be applied to the barrier layer 13 and baked to form a first layer, and then a coating liquid (coating agent) constituting the upper corrosion prevention treatment layer may be applied to the first layer and baked to form a second layer.

[0104] The degreasing treatment may be performed by spraying or immersion. The hydrothermal conversion treatment and anodizing treatment may be performed by immersion. The chemical conversion treatment may be performed by an appropriate method such as immersion, spraying, or coating, depending on the type of chemical conversion treatment.

[0105] Regarding the coating method of the coating agent having corrosion prevention properties, various methods such as gravure coating, reverse coating, roll coating, bar coating, etc. can be used.

[0106] As described above, the various treatments may be performed on either one or both sides of the metal foil, but in the case of one-sided treatment, the treated side is preferably the side on which the sealant layer 16 is laminated. If required, the surface of the base layer 11 may also be subjected to the above treatments.

[0107] The amount of coating agent applied to form the first layer and the second layer is 0.005 to 0.200 g / m 2 is preferable, and 0.010 to 0.100 g / m 2 is more preferred.

[0108] Furthermore, when dry curing is required, it can be performed at a base material temperature in the range of 60 to 300° C. depending on the drying conditions of the corrosion prevention treatment layers 14a and 14b used.

[0109] (Step of bonding the base layer 11 and the barrier layer 13) This step is a step of bonding the barrier layer 13 provided with the corrosion prevention treatment layers 14a, 14b to the base material layer 11 via the first adhesive layer 12a. The bonding method may be dry lamination, non-solvent lamination, wet lamination, or the like, and the two are bonded together using the material constituting the first adhesive layer 12a described above. The first adhesive layer 12a has a dry coating amount of 1 to 10 g / m. 2 More preferably, the range is 2 to 6 g / m 2 It is set within the range.

[0110] (Laminating step of second adhesive layer 12b and sealant layer 16) This step is a step of bonding the sealant layer 16 via the second adhesive layer 12b to the second corrosion prevention treatment layer 14b side of the barrier layer 13. Examples of the bonding method include a wet process and dry lamination.

[0111] In the case of the wet process, the solution or dispersion of the adhesive constituting the second adhesive layer 12b is applied onto the second corrosion prevention treatment layer 14b, and the solvent is removed at a predetermined temperature to form a dry film, or the dry film is baked as necessary after the dry film is formed. Then, the sealant layer 16 is laminated to produce the exterior material 10. Examples of the coating method include the various coating methods exemplified above. The preferred dry coating amount of the second adhesive layer 12b is the same as that of the first adhesive layer 12a.

[0112] In this case, the sealant layer 16 can be produced, for example, by a melt extrusion molding machine using a resin composition for forming a sealant layer that contains the above-mentioned components of the sealant layer 16. In the melt extrusion molding machine, the processing speed can be set to 80 m / min or more from the viewpoint of productivity.

[0113] (Aging process) This step is a step of aging (curing) the laminate. By aging the laminate, it is possible to promote adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the second adhesive layer 12b, and the sealant layer 16. The aging treatment can be carried out at a temperature in the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days.

[0114] In this manner, the exterior packaging material 10 of the present embodiment as shown in FIG. 1 can be manufactured.

[0115] Next, a description will be given of an example of a method for manufacturing the exterior material 20 shown in Fig. 2. Note that the method for manufacturing the exterior material 20 is not limited to the following method.

[0116] The manufacturing method of the exterior material 20 of this embodiment is generally configured to include a step of providing the corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a, a step of further laminating the adhesive resin layer 15 and the sealant layer 16 to prepare a laminate, and a step of heat treating the obtained laminate, if necessary. Note that the steps up to the step of bonding the base material layer 11 and the barrier layer 13 can be performed in the same manner as the manufacturing method of the exterior material 10 described above.

[0117] (Laminating Step of Adhesive Resin Layer 15 and Sealant Layer 16) This step is a step of forming an adhesive resin layer 15 and a sealant layer 16 on the second corrosion prevention treatment layer 14b formed in the previous step. The method includes a method of sand laminating the adhesive resin layer 15 together with the sealant layer 16 using an extrusion laminator. Furthermore, lamination is also possible by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded, or a co-extrusion method. In forming the adhesive resin layer 15 and the sealant layer 16, for example, each component is blended so as to satisfy the above-mentioned configuration of the adhesive resin layer 15 and the sealant layer 16. The above-mentioned resin composition for forming the sealant layer is used to form the sealant layer 16.

[0118] This process produces a laminate in which the layers are stacked in the following order: base layer 11 / first adhesive layer 12a / first corrosion prevention treatment layer 14a / barrier layer 13 / second corrosion prevention treatment layer 14b / adhesive resin layer 15 / sealant layer 16, as shown in FIG. 2.

[0119] The adhesive resin layer 15 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition using an extrusion laminator. Alternatively, the adhesive resin layer 15 may be laminated by extruding the granulated material, which has been melt-blended in advance using a melt kneading device such as a single-screw extruder, a twin-screw extruder, or a Brabender mixer, using an extrusion laminator.

[0120] The sealant layer 16 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition as the constituents of the resin composition for forming the sealant layer using an extrusion laminator. Alternatively, the adhesive resin layer 15 and the sealant layer 16 may be laminated by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded using an extrusion laminator using a granulated product obtained by melt blending in advance using a melt kneading device such as a single screw extruder, a twin screw extruder, or a Brabender mixer, or by a co-extrusion method. Alternatively, a sealant monolayer may be formed in advance as a cast film using the resin composition for forming the sealant layer, and this film may be laminated together with an adhesive resin by a method of sand lamination. The forming speed (processing speed) of the adhesive resin layer 15 and the sealant layer 16 may be, for example, 80 m / min or more from the viewpoint of productivity.

[0121] (Heat treatment process) This step is a step of heat-treating the laminate. Heat-treating the laminate can improve adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the adhesive resin layer 15, and the sealant layer 16. As a method of heat treatment, it is preferable to treat at a temperature at least equal to or higher than the melting point of the adhesive resin layer 15.

[0122] In this manner, the exterior packaging material 20 of this embodiment as shown in FIG. 2 can be manufactured.

[0123] Although preferred embodiments of the exterior material for a power storage device according to the present disclosure have been described in detail above, the present disclosure is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present disclosure as described in the claims.

[0124] The exterior material for an electricity storage device according to the present disclosure can be suitably used as an exterior material for an electricity storage device such as, for example, a secondary battery such as a lithium ion battery, a nickel-metal hydride battery, and a lead-acid battery, and an electrochemical capacitor such as an electric double layer capacitor, etc. In particular, the exterior material for an electricity storage device according to the present disclosure is suitable as an exterior material for an all-solid-state battery using a solid electrolyte.

[0125] [Electricity storage device] FIG. 3 is a perspective view showing one embodiment of a power storage device produced using the above-mentioned exterior material. As shown in FIG. 3, the power storage device 50 includes a battery element (power storage device main body) 52, two metal terminals (current extraction terminals) 53 for extracting current from the battery element 52 to the outside, and an exterior material 10 that hermetically encloses the battery element 52. The exterior material 10 is the exterior material 10 according to the present embodiment described above. In the exterior material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the exterior material 10 is configured to enclose the battery element 52 inside by folding one laminate film in two and heat-sealing it, or by overlapping and heat-sealing two laminate films, so that the base material layer 11 is on the outer side of the power storage device 50 and the sealant layer 16 is on the inner side of the power storage device 50. Note that the exterior material 20 may be used in place of the exterior material 10 in the power storage device 50.

[0126] Battery element 52 is formed by interposing an electrolyte between a positive electrode and a negative electrode. Metal terminal 53 is a part of a current collector taken out from exterior material 10, and is made of a metal foil such as copper foil or aluminum foil.

[0127] The electricity storage device 50 of this embodiment may be an all-solid-state battery. In this case, a solid electrolyte such as a sulfide-based solid electrolyte is used as the electrolyte of the battery element 52. Since the electricity storage device 50 of this embodiment uses the exterior material 10 of this embodiment, excellent laminate strength can be ensured even when used in a high-temperature environment. EXAMPLES

[0128] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.

[0129] [Materials used] The materials used in the examples and comparative examples are shown below.

[0130] <Base layer (thickness 25 μm)> Ny: A nylon (Ny) film (manufactured by Toyobo Co., Ltd.) having one side subjected to a corona treatment was used. PET: A polyethylene terephthalate film with one side subjected to a corona treatment was used.

[0131] <First adhesive layer> The first adhesive was prepared by mixing the base agent and curing agent shown in Table 1 so that the NCO / OH ratio was as shown in the table, and diluting with ethyl acetate to a solid content of 26% by mass. When two types of curing agents were used, they were mixed so that the ratio of NCO groups of each curing agent to the total NCO groups in the curing agent was the value shown in Table 1. Details of each component that makes up the first adhesive are as follows. (Main ingredient) Polyether polyol (AGC, product name: EXCENOL, product number: 837, hydroxyl value: 27 mg KOH / g) Polyester polyol (Hitachi Chemical Co., Ltd., product name: Teslac 2505-63, hydroxyl value: 7-11 mgKOH / g) Acrylic polyol (manufactured by Taisei Fine Chemical Co., Ltd., product name: 6KW-700, hydroxyl value: 10 mgKOH / g) Polycarbonate diol (PCD) (manufactured by Asahi Kasei Corporation, product name: Duranol T5651, hydroxyl value: 113 mg KOH / g) (hardening agent) IPDI-n: Isophorone diisocyanate nurate (Mitsui Chemicals, product name: Takenate 600) HDI-a: Hexamethylene diisocyanate adduct (manufactured by Asahi Kasei Corporation, product name: Duranate P301-75E) MDI polymer: Diphenylmethane diisocyanate polymer (manufactured by Tosoh Corporation, product name: Coronate 139) TDI-a: Tolylene diisocyanate adduct (Mitsui Chemicals, product name: Takenate 500)

[0132] <First corrosion prevention treatment layer (base layer side) and second corrosion prevention treatment layer (sealant layer side)> (CL-1): A sodium polyphosphate-stabilized cerium oxide sol was used, the solid content of which was adjusted to 10% by mass using distilled water as a solvent. The sodium polyphosphate-stabilized cerium oxide sol was obtained by mixing 100 parts by mass of cerium oxide with 10 parts by mass of sodium salt of phosphoric acid. (CL-2): A composition consisting of 90% by mass of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" adjusted to a solid content concentration of 5% by mass using distilled water as a solvent, and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation)" was used.

[0133] <Barrier layer (thickness 40 μm)> Either annealed and degreased soft aluminum foil (manufactured by Toyo Aluminum, "8079 material") or copper foil (manufactured by JX Metals, model number: HA) was used.

[0134] <Second adhesive layer (coating amount 3g / m 2 )> A polyurethane adhesive was used, which was prepared by mixing polyisocyanate with acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane.

[0135] <Sealant layer (thickness 80 μm)> A polyolefin film (a non-oriented polypropylene film with the surface facing the second adhesive layer subjected to a corona treatment) was used.

[0136] [Creating exterior materials] Example 1 The barrier layer (aluminum foil) was attached to the base layer (nylon) using the first adhesive (first adhesive layer) by dry lamination. The barrier layer and base layer were laminated by applying the first adhesive to one side of the barrier layer so that the applied amount (mass per unit area) after drying was the value shown in Table 1, drying at 80°C for 1 minute, laminating it with the base layer, and aging it at 80°C for 120 hours.

[0137] Next, the surface of the barrier layer opposite the substrate layer side was attached to a sealant layer (thickness 80 μm) by dry lamination using a polyurethane adhesive (second adhesive layer). The lamination of the barrier layer and the sealant layer was performed by applying a polyurethane adhesive to the surface of the barrier layer opposite the substrate layer side in an amount (mass per unit area) of 3 g / m2 after drying. 2 After drying at 80° C. for 1 minute, the laminate was attached to a sealant layer and aged for 3 hours at 120° C. In this manner, an exterior material (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was produced.

[0138] (Examples 2 to 17) Exterior materials of Examples 2 to 17 (laminates of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) were prepared in the same manner as in Example 1, except that at least one of the composition of the first adhesive and the application amount of the first adhesive was changed as shown in Table 1.

[0139] (Example 18) An exterior material of Example 18 (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was produced in the same manner as in Example 1, except that the material of the barrier layer was copper foil (Cu) and the composition of the first adhesive and the amount of the first adhesive applied were changed as shown in Table 1.

[0140] (Examples 19 to 21) Except for using aluminum foil as the barrier layer and changing its thickness as shown in Table 1, the exterior materials of Examples 19 to 21 (laminates of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) were prepared in the same manner as in Example 18.

[0141] Example 22 An exterior material of Example 22 (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was prepared in the same manner as in Example 16, except that no corrosion prevention layer was provided on the barrier layer.

[0142] (Example 23) An exterior material of Example 23 (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was produced in the same configuration as Example 16, except that the substrate was PET.

[0143] (Comparative Examples 1 and 2) Exterior materials of Comparative Examples 1 and 2 (laminates of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) were prepared in the same manner as in Example 1, except that the composition of the first adhesive was changed as shown in Table 1.

[0144] [IR measurement] The exterior material was cut to an appropriate size, and a trigger was created from the edge to peel off the base layer and the barrier layer. When measuring the attenuated total reflection (ATR) of the Fourier transform infrared (FT-IR) spectroscopy from the surface of the side where the adhesive layer remains more, the infrared wave number was found to be the baseline transmittance T0 and the 2200 cm -1 From 2300cm -1 The minimum transmittance T1 detected in the range of 1670cm -1 From 1710cm -1 The minimum transmittance T2 detected within the range was calculated. Each calculated value was evaluated to see if it satisfied the relationship 0.06≦(T0-T1) / (T0-T2)≦0.4. The results are shown in Table 1. Measurement conditions: Prism: Germanium Wavenumber resolution: 4cm -1 Number of times: 4 Baseline: Wavenumber 2500-2700cm -1 The average intensity between the <Measuring Equipment> PerkinElmer: Spectrum Spotlight 400

[0145] [Table 1]

[0146] [Evaluation of heat-resistant laminate strength on exterior side] The barrier layer and base layer of the exterior material cut to a width of 15 mm were peeled off. Measurements were performed by a 90-degree peel test using a tensile tester (manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min. In the following evaluations, a rating of △ or higher is considered to be a pass. (Laminate strength at room temperature) The laminate strength was measured under a room temperature (25° C.) environment. Based on the obtained laminate strength, the laminate was evaluated according to the following criteria. The results are shown in Table 2. ◎: Lamination strength is 6.0N / 15mm or more. Good: Laminate strength is 4.5N / 15mm or more and less than 6.0N / 15mm. △: Laminate strength is 3.0N / 15mm or more and less than 4.5N / 15mm. ×: Lamination strength is less than 3.0N / 15mm.

[0147] (Laminate strength in high temperature environments) The exterior material cut to a width of 15 mm was left in a high-temperature environment at 150°C for 5 minutes. The laminate strength was then measured in the 150°C environment. The laminate strength was evaluated according to the following criteria. The results are shown in Table 2. ◎: Lamination strength is 3.5N / 15mm or more. Good: Laminate strength is 2.5N / 15mm or more and less than 3.5N / 15mm. △: Laminate strength is 2.0N / 15mm or more and less than 2.5N / 15mm. ×: Lamination strength is less than 2.0N / 15mm.

[0148] [Evaluation of deep drawing formability] The molding depth at which deep drawing was possible for exterior materials was evaluated by the following method. The molding depth of the molding device was set to 1.00 to 5.00 mm in increments of 0.25 mm, and the exterior materials were deep-draw molded. The samples after deep drawing were visually checked for the presence or absence of breaks and pinholes while shining a light on the samples, and the maximum molding depth at which deep drawing was possible without the occurrence of either breaks or pinholes was determined. The molding depth was also evaluated according to the following criteria. The results are shown in Table 2. ◎: The maximum molding depth is 5.00 mm or more. ○: The maximum molding depth is 4.00 mm or more and less than 5.00 mm. △: The maximum molding depth is 3.00 mm or more and less than 4.00 mm. ×: The maximum molding depth is less than 3.00 mm.

[0149] [Evaluation of deep drawing reliability] The samples (five specimens each) with a mold depth of 2.00 mm prepared for the above deep drawability evaluation were stored in an environment at 150°C for one week. After that, the samples were visually inspected while shining a light on the vicinity of the molded convex portion to check the occurrence of delamination between the base layer and the barrier layer. In addition, the environmental reliability was evaluated according to the following criteria. The results are shown in Table 2. ○: Delamination did not occur in any of the five samples. ×: Delamination occurred in one or more of the five samples.

[0150] [Table 2] [Industrial Applicability]

[0151] According to the present disclosure, there are provided an exterior material for a power storage device that can ensure excellent laminate strength both in room temperature and high temperature environments and also has excellent deep draw formability, and a power storage device using the same. [Explanation of symbols]

[0152] Reference Signs List 10, 20... exterior material for electricity storage device, 11... base material layer, 12a... first adhesive layer, 12b... second adhesive layer, 13... barrier layer, 14a... first corrosion prevention treatment layer, 14b... second corrosion prevention treatment layer, 15... adhesive resin layer, 16... sealant layer, 50... electricity storage device, 52... battery element, 53... metal terminal

Claims

1. The laminate includes at least a base layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a sealant layer in this order, The base material layer is removed to expose the first adhesive layer. When the exposed adhesive layer is measured from the outermost surface side by attenuated total reflection of Fourier transform infrared spectroscopy, the transmittance of the baseline T0 and the transmittance of the first adhesive layer at 2100 cm -1 From 2400 cm -1 The minimum transmittance T1 detected in the range of 1670 cm -1 From 1700cm -1 The minimum transmittance T2 detected within the range satisfies the relationship 0.06≦(T0−T1) / (T0−T2)≦0.

4.

2. A power storage device main body; a current extracting terminal extending from the power storage device body; The exterior packaging material for an electricity storage device according to claim 1 , which holds the current extracting terminal and houses the electricity storage device body; A power storage device comprising:

Citation Information

Patent Citations

  • Layered package material, outer package material for battery, and the battery

    JP2008287971A

  • Exterior package material for power storage device, and power storage device

    JP2019117706A

  • External facing material for power storage device

    JP2013101765A